THE CORRELATION OF OMEGA 3 LEVELS WITH INTERLEUKIN-6 LEVELS IN A HEALTHY ELDERLY COMMUNITY RSMH PALEMBANG - Khoirun Putra; Nur Riviati (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Ageing is associated with the geriatric syndrome, characterized by several health issues frequently associated with immunosenescence. In the elderly, immunosenescence is characterized by low-grade chronic systemic inflammation manifested as elevated levels of inflammatory molecular and cellular markers. One of the inflammatory markers is interleukin 6 (IL-6). In addition, omega-3 polyunsaturated fatty acids are a class of biologically active and anti-inflammatory fatty acids. This study aims to determine the relationship between omega-3 and interleukin-6 levels in the elderly in RSMH Palembang who are in good health. This investigation is a cross-sectional, analytic observational study. The sampling method employed was consecutive sampling. The participants in this study were members of the RSMH Palembang healthy elderly community who were 60 years of age or older. People who were malnourished, had severe illnesses like cancer or autoimmune diseases, or were taking Omega-3 supplements were not allowed in this study. As a result, 22 (55%) of 40 research subjects had low serum omega-3 levels. On the other hand, there were 35 (87.5%) samples with elevated serum IL-6 levels and 5 (12.5%) samples with normal IL-6 levels among the samples obtained. The correlation analysis showed that there was a strong negative correlation between the levels of serum omega-3 and interleukin 6 (p = 0.005). Omega 3 levels and interleukin-6 levels are correlated in the healthy elderly population of RSMH Palembang.